STUDI KEBERADAAN BERBAGAI JENIS BURUNG DI WAHANA EKOWISATA MANGROVE SUNGAI RAWA KECAMATAN SUNGAI APIT - Darwis Gidion; Defri Yoza; Viny Volcherina Darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Mangrove Ecotourism Rawa River is a mangrove forest that remains on the East Coast of Sumatra Island that has a high conservation value. This mangrove forest becomes a place for flora and fauna that live interconnected. This research aims to find out the diversity of bird species in mangrove ecotourism sungai rawa. Research data collection uses the IPA (Index Point of Abundance) and Rapid Assessment Methods by observation to obtain data directly in the region. The data was analyzed using formulations of type diversity, type equality, type similarity and abundance of types. Based on data processing obtained 20 types of birds from 13 bird families, namely, Centropus bengalensis, Pycnonotus cyaniventris, Dinopium javanense, Prinia familiaris, Granulax lugubris, Collocalia esculenta, Treron fulvicollis, Eudynamys saturates, Picus vittatus, Acridotherestristis, Zosterops palpebrosus, Rhipidura javanica,Geopelia striata, Ixobrychus eurhythmus, Butorides striatus, Todirhamphus sanctus, Celeus brachyurus,Picoides moluccensis), Cikalang, Tringa brevipes. With the magnitude of each diversity index on land zoning 2.36, central zonation 2.76, coastal zonation 1.93. For the type leveling index on land zonation 0.02, central zonation 0.02, coastal zonation 0.05. The type similarity index is classified as high with a magnitude of 57 %-97% and for the abundance of middle zonation types is highest with the number of 20 types. Keywords: Mangrove Ecotourism  Sungai Rawa, diversity of birds, species richness